2021
DOI: 10.3389/fneur.2021.704088
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Factor Analyses of Futile Recanalization in Acute Ischemic Stroke Patients Treated With Mechanical Thrombectomy

Abstract: Background and Purpose: Acute ischemic stroke (AIS) is a serious threat to the life and health of middle-aged and elderly people. Mechanical thrombectomy offers the advantages of rapid recanalization, but the response of patients to this treatment varies greatly. This study investigated the risk factors for futile recanalization in AIS patients after thrombectomy through multivariate analyses.Methods: A retrospective study was conducted in AIS patients with anterior circulation occlusion from a derivation coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 39 publications
6
31
0
Order By: Relevance
“…Consistent with most previous studies ( 5 , 10 12 , 14 ), we found that advanced age was associated with functional dependence despite successful recanalization, which may be explained by the higher prevalence of underlying diseases, higher incidence of complications, and lower potential for rehabilitation in older age groups compared with younger ones. In addition, older adults are more likely to have leukoaraiosis and poor collateral status than younger individuals, which may be linked to the occurrence of intracranial hemorrhage and poor outcomes after successful reperfusion ( 15 ).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with most previous studies ( 5 , 10 12 , 14 ), we found that advanced age was associated with functional dependence despite successful recanalization, which may be explained by the higher prevalence of underlying diseases, higher incidence of complications, and lower potential for rehabilitation in older age groups compared with younger ones. In addition, older adults are more likely to have leukoaraiosis and poor collateral status than younger individuals, which may be linked to the occurrence of intracranial hemorrhage and poor outcomes after successful reperfusion ( 15 ).…”
Section: Discussionsupporting
confidence: 91%
“…The final cohort included 2261 patients: median (IQR) age 75 years (64-83), 46% female, median NIHSS 9 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). 34% received IVT alone, 41% MT alone and 25% both acute recanalization treatments (bridging approach).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…All patients had a clinically confirmed diagnosis of AIS with LVO of the anterior circulation and underwent EVT according to the standard of care using stentretrievers and/or aspiration catheters at the Department of Neurology at Nanjing First Hospital. Patients were selected if they fulfilled the following criteria: (1) age 18 years or older; (2) LVO in the anterior circulation, including the internal carotid artery (ICA), M1/M2 segment of the middle cerebral artery (MCA); (3) successful recanalization [defined as modified Thrombolysis In Cerebral Infarction (mTICI) scale grades 2b or 3]; (4) premorbid modified Rankin Scale (mRS) score ≤ 2; (5) known National Institutes of Health Stroke Scale (NIHSS), ASPECTS, and mRS score at 90 days; (6) time from onset to puncture ≤ 6 or 6-24 h with evidence of perfusion mismatch. Patients who missed more than one data were to be excluded.…”
Section: Study Design and Populationmentioning
confidence: 99%